Impact of Near Work Activity on Visual Acuity among Junior High School Students - Raisha Pratiwi Indrawati; Reni Farenia; Mayasari Wahyu Kuntoyo (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Uncorrected refractive error is experienced by at least 45 million productive-aged adults (aged 16–45 years old) and 13 million children (aged 5–15 years old), and being the main cause of visual impairment in children worldwide and third cause of blindness in any age in Indonesia. Near work activity is estimated as one of environmental risk factor causing this refractive error, leading into decreased visual acuity. This study was conducted to analyse the impact of near work activity on visual acuity among junior high school students in JatinangorMethods: This study was conducted in junior high school in Jatinangor, using cross sectional method. Total of 147 subjects were screened for visual impairment using Rapid Assessment of Avoidable Blindness (RAAB) tumbling E chart and assesed for near work activity using questionnaire-guided interview method after informed consent had been obtained. Data were analysed using unpaired-T test and Mann-Whitney test.Results: Total diopter hours of near work activity among the group with visual acuity ≥6/18 and group with visual acuity <6/18 showed no significant difference (p=0.329), with latter group had less time-spent in near work activity. Similarly, each activity such as reading, watching TV, and using computer also showed no significant difference , except for playing games where the group with better visual acuity had shown significantly longer time spent than another group (p=0.018).Conclusions: Near work activity does not have impact on visual acuity among junior high school students, except for playing games.[AMJ.2016;3(1):38–42] DOI: 10.15850/amj.v3n1.700